Portuguese community pharmacists' attitudes to and knowledge of antibiotic misuse: questionnaire development and reliability. - Fátima Roque (Public Library of Science (PLoS), 2014)
Objective To develop and evaluate the reliability of a self-administered questionnaire designed to assess the attitudes and knowledge of community pharmacists in Portugal about microbial resistance and the antibiotic dispensing process. Methods This study was divided into the following three stages: (1) design of the questionnaire, which included a literature review and a qualitative study with focus-group sessions; (2) assessment of face and content validity, using a panel of experts and a pre-test of community pharmacists; and, (3) pilot study and reliability analysis, which included a test-retest study covering fifty practising pharmacists based at community pharmacies in five districts situated in Northern Portugal. Questionnaire reproducibility was quantified using the intraclass correlation coefficient (ICC; 95% confidence interval) computed by means of one-way analysis of variance (ANOVA). Internal consistency was evaluated using Cronbach's alpha. Results The correlation coefficients were fair to good (ICC>0.4) for all statements (scale-items) regarding knowledge of and attitudes to antibiotic resistance, and ranged from fair to good to excellent for statements about situations in which pharmacists acknowledged that antibiotics were sometimes dispensed without a medical prescription (ICC>0.8). Cronbach's alpha for this section was 0.716. Conclusions The questionnaire designed in this study is valid and reliable in terms of content validity, face validity and reproducibility.